Cancer Panel Sequencing to Guide Personalized Therapy of Breast and Gynecologic Cancers [32A]. (May 2018) - Li, Shuyu; Gross, Susan Joy; Donovan, Michael; Sebra, Robert; Housman, Laura; Chen, Rong
Abstract : INTRODUCTION: Recent genomic studies have demonstrated significant heterogeneity in breast and gynecologic cancers, characterized by distinctive genomic profiles in individual patients that could affect treatment responses. The aim of this study was to determine what percentage of patients may have findings that are of potential clinical consequence. METHODS: We analyzed 56 tumor samples from 32 breast cancers and 24 gynecologic cancers (ovarian, uterine, cervical) using the Ion AmpliSeq Hotspot Panel v2 or the Oncomine Comprehensive Assay v2 to identify somatic mutations. We also generated copy number alteration and RNA-sequencing data to further characterize the tumors. RESULTS: TP53 was the most frequently mutated genes in this cohort, consistent with genomic sequencing studies by TCGA and ICGC. Mutations with therapeutic implications were identified in many cases. PI3-Kinase pathway is likely activated in 31% and 42% of the breast and gynecologic cancers respectively due to PIK3CA activating mutations, PTEN loss and/or TSC1 loss. We also observed EGFR exon-20 insertions in 3 breast tumor samples, representing a novel mechanism of activating the ERK pathway in breast cancers. CONCLUSION: Given that everolimus has been approved by the FDA for post-menopausal, advanced hormone-receptor positive, HER2-negative breast cancers, and in light of recent promising results from several clinical trials of PI3-Kinase pathway inhibitors in breast, ovarian, and uterine cancers, breast and gynecologic cancer panel sequencing in precision oncology holds promise for more directed therapies, clinical trial recruitment and future research.